2016
DOI: 10.1007/s40333-016-0017-8
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal patterns in water uptake for Medicago sativa grown along an elevation gradient with shallow groundwater table in Yanchi county of Ningxia, Northwest China

Abstract: Lucerne (Medicago sativa L.) is a deep-rooted perennial leguminous forage with high evapo-transpiration rate exceeding the annual precipitation in semi-arid areas of Northwest China. Groundwater might be the potential water sources of lucerne in the area with shallow groundwater table. In this study, stable isotopic compositions of oxygen and hydrogen (δ 18 O and δD) of different water sources and xylem sap were analyzed to determine the seasonal (April, June, July and August) and topographic (three slope posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…3 and 4). These results agree with the general conclusions of previous studies (e.g., Kitzler et al, 2006;Singh et al, 2010;Butterbach-Bahl et al, 2013;Zhu et al, 2016). Therefore, it may be prevalent that CO 2 and N 2 O effluxes start to increase in spring and peak in summer (Fig.…”
Section: Ghgsupporting
confidence: 92%
See 1 more Smart Citation
“…3 and 4). These results agree with the general conclusions of previous studies (e.g., Kitzler et al, 2006;Singh et al, 2010;Butterbach-Bahl et al, 2013;Zhu et al, 2016). Therefore, it may be prevalent that CO 2 and N 2 O effluxes start to increase in spring and peak in summer (Fig.…”
Section: Ghgsupporting
confidence: 92%
“…First, alfalfa with rhizobia, the root-dwelling symbiotic bacteria, can fix atmospheric N 2 (Peterson & Russelle, 1991) and thus reduce N fertilizer applications. Secondly, due to its strong ability to take up water (Wan et al, 2008), the alfalfa is mostly (>75%) planted in the Northwest inland regions with an arid or semi-arid climate in or around the Loess Plateau of China (Hu & Cash, 2009;Wang, Hansen & Xu, 2016); however, alfalfa has a much higher water requirement than other crops which may deplete soil water and aggravate soil desiccation in long-term stands (Guan et al, 2013;Zhu et al, 2016). For example, McCallum, Peoples & Connor (2000) reported that in Australia soil profiles under alfalfa-based perennial fields remain consistently drier throughout the year compared with continuous annual cropping.…”
Section: Introductionmentioning
confidence: 99%
“…Basically, this approach represents the plant root system as one unique root (Rothfuss & Javaux, 2017). IsoSource (Phillips & Gregg, 2003) is a widely used linear mixing model based on a mass balance equation (recent examples are Jia, Liu, Chen, & Yu, 2017;Zhu, Zhang, Gao, Qi, & Xu, 2016). Nowadays, statistical Bayesian mixing models such as SIAR (Parnell et al, 2013), MixSir, and MixSIAR (Moore & Semmens, 2008) are gaining popularity (e.g., Beyer, Hamutoko, Wanke, Gaj, & Koeniger, 2018).…”
mentioning
confidence: 99%
“…As soil water is the flowing medium of material and energy in the soil system, study on soil water transportation is important for the migration of nutrition and pollutants, the generation of runoff, and the recharge of underground water [88]. The recharge sources of soil water include precipitation, groundwater, irrigation water, and small amount of moisture condensation, and soil water dissipation ways mainly include evaporation [89], transpiration [90], water drainage, and runoff. By analyzing δD and δ 18 O of soil water, we can understand soil water's evapotranspiration [91], transit mechanism [20], residence time [92], transference, and transition with groundwater [93].…”
Section: Water Stable Isotope Characteristics Of Rmsmentioning
confidence: 99%